Advanced Polymers for Reduced Energy Consumption in Architecture. Issue 3 (22nd November 2018) - Heifferon, Katherine V.; Long, Timothy E.
Abstract: In an effort to slow the progress of climate change, the current scientific community has focused on the reduction of greenhouse gases in order to limit the global average temperature inflation to less than 2 °C. The improvement of thermally controlled construction materials can potentially result in lower energy homes/reduced emissions, and lowering the thermal conductivity of insulation materials improves home energy efficiency. Nanoporous insulation foams impart a drastic decrease in thermal conductivity but many polymer properties must be assessed to produce these materials. Passive phase‐change materials also represent another key energy‐saving device to control heat flux within a living space. Research into unique polymeric systems provides a novel means of encapsulation or creating polymeric cross‐linked matrices to prevent leakage and improve mechanical robustness. These two areas of polymer research in architecture represent key advancements for construction materials aimed toward energy savings and energy‐related emissions control. Abstract : Modern insulation materials developed through polymer‐focused research represent significant improvements in the field of energy‐efficient construction materials. Nanoporous foams and phase‐change materials improve insulation efficiency and eliminate the influence of human intervention in the heating and cooling of homes. This review encompasses the structure–property relationships of polymers utilized in these two areas of insulation advancement.